Bacterial contaminants and spoilage of South African beers - Van Vuuren, H. J. J.(Hendrik Jurgens Jansen),1946- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1976.